Examining concurrent validity and item selection of the Session Wants and Needs Outcome Measure (SWAN-OM) in a children and young people web-based therapy service - De Ossorno Garcia, Santiago; Edbrooke-Childs, Julian; Salhi, Louisa; Ruby, Florence J. M.; Sefi, Aaron; Jacob, Jenna (Frontiers in Psychiatry, 2023)
Background: Single-session mental health interventions are frequently attended by children and young people in both web-based and face-to-face therapy settings. The Session “Wants” and “Needs” Outcome Measure (SWAN-OM) is an instrument developed in a web-based therapy service to the overcome challenges of collecting outcomes and experiences of single-session therapies. It provides pre-defined goals for the session, selected by the young person prior to the intervention, on which progress towards achievement is scored at the end of the session. Objective: To evaluate the instrument’s psychometric properties, including concurrent validity against three other frequently used outcome and experience measures, at one web-based mental health service using text-based support. Methods: The SWAN-OM was administered for a period of six months to 1401 children and young people (aged 10 to 32; 79.3% White; 77.59% female) accessing single-session therapy in a web-based service. Item correlations with comparator measures and hierarchical logistic regressions to predict item selection were calculated for concurrent validity and psychometric exploration. Results: Most frequently selected items are “Feel better” (N= 431; 11.61%) and “Find ways I can help myself” (N= 411; 11.07%); unpopular items are “Feel safe in my relationships” (N= 53; 1.43%) and “Learn the steps to achieve something I want” (N= 58; 1.56%). The SWAN-OM is significantly correlated with the Experience of Service Questionnaire, particularly the item: “Feel better”(rs(109) = .48, p < .001), the Youth Counselling Impact Scale, particularly the item: “Learn the steps to achieve something I want” (rs(22) = .76, p < .001), and the Positive and Negative Affect Schedule, particularly the items: item “Learn how to feel better” (rs(22) = .72, p < .001) and were “Explore how I feel” (rs(70) = -.44, p < .001). Conclusions: The SWAN-OM demonstrates good concurrent validity with common outcome and experience measures. Analysis suggests that lesser endorsed items may be removed in future iterations of the measure, to improve functionality. Future research is required to explore SWAN-OM’s potential to measure meaningful change, in a range of therapeutic settings.